Farmer participatory research and soil conservation in Southeast Asian cassava systems - Dalton, Timothy J.; Lilja, N.K.; Johnson, Nancy L.; Howeler, Reinhardt H. (Elsevier, 2011)
This paper examines the impact of participatory research and tests hypotheses on its effectiveness to increase the adoption of soil conservation and fertility management innovations in Southeast Asia. Participatory research activities are significant and positive in explaining the differential adoption rates of hedgerows, contour ridging, the usage of farm yard manure, and inorganic fertilizer over nonparticipants. Secondly, the impacts of the participatory approach on soil conservation and fertility management innovations are incorporated into models examining the reasons for change in land allocation and cassava yields. Results are mixed. We also find a positive impact to participatory research and extension activities on cassava yield that is not linked to new technology adoption.